2021
DOI: 10.1002/for.2785
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid fine particulate matter (PM2.5) forecasting and its further application system: Case studies in China

Abstract: Air pollution has received more attention from many countries and scientists due to its high threat to human health. However, air pollution prediction remains a challenging task because of its nonstationarity, randomness, and nonlinearity. In this research, a novel hybrid system is successfully developed for PM 2.5 concentration prediction and its application in health effects and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The research findings indicated that the combination of SO and ELM in a hybrid model performed significantly better than using a single ELM for predicting PM 2.5 concentration. These results align with other scientific papers published in the literature, which have also shown that hybrid models provide improved prediction performance for simulating air pollution parameters 60 62 . Additionally, the SO algorithm enhances the prediction accuracy of the standard ELM by determining optimal weights and bias values.…”
Section: Resultssupporting
confidence: 91%
“…The research findings indicated that the combination of SO and ELM in a hybrid model performed significantly better than using a single ELM for predicting PM 2.5 concentration. These results align with other scientific papers published in the literature, which have also shown that hybrid models provide improved prediction performance for simulating air pollution parameters 60 62 . Additionally, the SO algorithm enhances the prediction accuracy of the standard ELM by determining optimal weights and bias values.…”
Section: Resultssupporting
confidence: 91%
“…Machine learning (ML) has made tremendous progress in recent years in solving numerous engineering in general [27][28][29][30][31][32] and PM 2.5 concentration in particular [33][34][35][36][37][38][39][40][41][42]. ML combines data science, statistics, and computing in an interdisciplinary fashion.…”
Section: Previous Workmentioning
confidence: 99%
“…In another work, the author successfully created a new hybrid model for predicting PM 2.5 levels in outdoors and its use in assessing health consequences and economic losses. According to the authors, the suggested model not only provides early warning information but may also be employed in other systems such as health difficulties [91]. Furthermore, Augustine et al, proposed Ensemble machine learning approaches for predicting and forecasting PM 2.5 concentrations (e.g., XGBoost-RF-ARIMA).…”
Section: Particulate Matter Forecasting Using Ai Techniquesmentioning
confidence: 99%